Imagem: do não-saber a uma epistemologia crítica - Martinelli, Paula (2022)
The academic debate about the image of art makes evident its complex substance. This thesis intends to contribute to the recent discussions, using the theoretical perspectives found in semiotics and psychoanalysis in order to treat the image as a phenomenon immersed into relations of production and communication; an interface of exchange between subjects; movement that becomes presence in different spatiotemporal contexts. This thesis privileges an interdisciplinary approach that reconciles academic knowledge and artistic practices, exploring interactions as non-linear, inferential and meaning-generating. The present work also suggests the deepening of theoretical linkages, highlighting possible paths for an epistemology of the image that can be compatible with artistic procedures and with the idea of authorship, which finds in the critique of creation processes the theoretical the necessary support to be treated as a path of psychic constitution and organization. For this purpose, the symbol is highlighted as the key element that connects propositions found in psychoanalysis – mainly with Freud, as well as several post-Freudian authors – and Peircean semiotics; from the concepts that surround the idea of symbol emerges a broad understanding towards the significant function exerted by subjects and images